Comparative analysis of chronic neuropathic pain and pain assessment in companion animals and humans - Parker, Rell L. (Frontiers in Veterinary Science, 2024)
Chronic neuropathic pain is underdiagnosed in companion animals. This paper will review the definition of pain and how classification and grading of neuropathic pain can be applied from human to veterinary medicine to increase the recognition of and the confidence in a neuropathic pain diagnosis. The mechanisms of nociception and the pathophysiology of the sensory systems that underlie the transition to chronic pain are described. Potential future methods for diagnosis and treatment of neuropathic pain in veterinary medicine are considered, utilizing the theoretical framework of pain behavior from humans and rodents. By discussing the current state of pain diagnosis in companion animals and increasing the recognition of chronic neuropathic pain, the goal is to increase understanding of chronic neuropathic pain in daily clinical practice and to aid the development of methods to diagnose and treat neuropathic pain.